Shaping the directionality of sustainability transitions: the diverging development patterns of solar photovoltaics in two Chinese provinces - Yang, Kejia; Schot, Johan; Truffer, Bernhard (Regional studies, 2022)
This paper investigates how actors across spatial levels shape the directions of transition. We examine two Chinese provinces, Inner Mongolia and Jiangsu, with contrasting directionalities of solar photovoltaic (PV) development. The former developed PV as part of the large-scale centralized power system, and the latter focused on PV development as a core element of an alternative distributed form of power generation. We argue that three aspects have been key for understanding the divergent patterns: the specific portfolio of enacted institutional work; the type of interactions between niche and regime actors; and the selective leveraging of national institutional conditions by provincial actors.